C. S. Lewis's Perelandra : Reshaping the Image of the Cosmos - Wolfe, B. N. (Brendan N.); Wolfe, Judith (Judith E.) (Book collections on Project MUSE., 2013)
C. S. Lewis considered his novel Perelandra (1943) among his best works. A triumph of imaginative science fiction, Perelandra - the second volume of Lewis's "Space Trilogy" - is also theologically ambitious. This book explores how the novel synthesizes the three traditions of cosmology, mythology, and Christianity. The first group of essays considers the cosmological implications of the world Lewis depicts in Perelandra, while the second group examines the relationship between morality and meaning in Lewis's created cosmology of the planet Perelandra. This work brings together a world-class group of literary and theological scholars and Lewis specialists that includes Paul S. Fiddes, Monika B. Hilder, Sanford Schwartz, Michael Travers, and Michael Ward. The collection is enhanced by Walter Hooper's reminiscences of his conversations with Lewis about Perelandra and the possible provenance of the stories in Lewis's imagination. Lewis scholars and devoted readers alike will find this volume to be of help in understanding this canonical work of speculative fiction.